Editorial - Camacho Zegarra, María Augusta (Universidad ESAN, 2020)
Ten years ago we focused on the project of starting a law degree Corporate at ESAN University, to lay its foundations and put it, finally, available to young people eager to study a career in quality that combines the classic aspects of law with the introduction knowledge of the field of management and business, as well as the area international with an economic perspective. According to the great objective of make it one of the best options to train corporate lawyers, the desire arose to materialize a work that constituted a space for the reflection, analysis and intellectual production of our teachers, students, researchers or jurists in general.

Hace diez años nos centramos en el proyecto de iniciar la carrera de Derecho Corporativo en la Universidad ESAN, de asentar sus cimientos y de ponerla, finalmente, a disposición de los jóvenes ansiosos de estudiar una carrera de calidad que combinara los aspectos clásicos del derecho con la introducción de conocimientos del ámbito de la gestión y de los negocios, así como del área internacional con una perspectiva económica. Acorde con el gran objetivo de convertirla en una de las mejores opciones para formar abogados corporativos, surgió el anhelo de concretar una obra que constituyera un espacio para la reflexión, el análisis y la producción intelectual de nuestros profesores, estudiantes, investigadores o juristas en general.
Keywords: Editorial; Editorial; https://purl.org/pe-repo/ocde/ford#5.05.01